Equity in Education Financing: The Case of Turkey - Elene Murvanidze (International Journal of Contemporary Economics and Administrative Sciences, 2024)
This study investigates the burden of out-of-pocket education expenditures on households in Turkey. To measure equity in education financing we follow a conceptual framework outlined by UNESCO (2018) and utilize approaches previously used in assessing health equity. Following Wagstaff et al.’s (2008) approach, we first calculate education expenditure as a share of Ability-to-Pay (ATP), and then utilize the Lorenz dominance analysis to compare the distribution of these education expenditures with the distribution of income. Lastly, we calculate Kakwani indices and measure the magnitude of progressivity. The results indicate that from 2004 to 2012, education expenditures as a share of three different proxies of the standard of living (disposable income, market income, and total expenditure) increased for every income quintile. Based on the Lorenz dominance analyses, the low-income group’s share of income is often lower than its share of education expenditures – suggesting regressive education financing. Comparing expenditures by levels of education shows that primary education financing is progressive, whereas tertiary education financing is regressive. The results indicate that the provision of education policies in and of itself is not sufficient for attaining a more equitable education system.